The Relationship Between Health Belief Model on Covid-19 Preventive Behavior in The Elderly - Fitriani, Fitriani; Nih Farisni, Teungku; Yarmaliza, Yarmaliza; Reynaldi, Fitrah; Zakiyuddin, Zakiyuddin (International Journal of Social Science, Education, Communication and Economics, 2022)
Indonesia is one of the countries affected by the COVID-19 pandemic. The elderly are the group most at risk for morbidity and mortality due to COVID-19. West Aceh Regency is one of the areas with confirmed cases of COVID-19. This study aims to analyze the behavior of preventing COVID-19 in the elderly group. This type of research is descriptive analytic, with a quantitative approach. The sampling technique used was total sampling. Data collection techniques using a questionnaire instrument. Data analysis in this study used three analyzes, namely univariate, bivariate, and multivariate. The results showed that 69.8% of the elderly with less Perceived Susceptibility but had good COVID-19 prevention. 64.7% of the elderly with good Perceived Severity but have less prevention. 63.6% of respondents have good Perceived Benefits as well as COVID-19 prevention. 69.1% of respondents have less Perceived Barriers but have good COVID-19 prevention and 69.1% have good Cues to action plus good COVID-19 Prevention. The most dominant factors that can be used in COVID-19 prevention are Perceived Severity with an OR value of 2.77 and Perceived Barriers with an OR value of 2.76. The Health Belief Model has a relationship and can cause behavioral changes in preventing the potential for COVID-19 in the elderly.